Transcriptome Analysis Reveals Differentially Expressed Genes and Long Non-coding RNAs Associated With Fecundity in Sheep Hypothalamus With Different FecB Genotypes - Chen, Si; Guo, Xiaofei; He, Xiaoyun; Di, Ran; Zhang, Xiaosheng; Zhang, Jinlong; Wang, Xiangyu; Chu, Mingxing (Frontiers in Cell and Developmental Biology, 2021)
Small Tail Han sheep, with different FecB genotypes, manifest distinct ovulation rate and fecundities, which are due to differences in reproductive hormones secreted by the hypothalamic–pituitary–ovarian axis. Nevertheless, the function of the hypothalamus against a FecB mutant background on increasing ovulation rate has rarely reported. Therefore, we determined the expression profiles of hypothalamus tissue collected from six wild-type (WW) and six FecB mutant homozygous (BB) ewes at follicular and luteal phases by whole-transcriptome sequencing. We identified 53 differentially expressed mRNAs (DEGs) and 40 differentially expressed long non-coding RNAs (DELs) between the two estrus states. Functional annotation analysis revealed that one of the DEGs, PRL, was particularly enriched in the hypothalamic function, hormone-related and reproductive pathways. The lncRNAs–target genes interaction networks and KEGG analysis in combination suggested that the lncRNAs LINC-676 and WNT3-AS cis-acting on DRD2 and WNT9B in different phases may induce GnRH secretion. Furthermore, there were differences of regulatory elements and WNT gene family members involved in the follicular–luteal transition in the reproductive process between wild type (WNT7A) and FecB mutant sheep (WNT9B). We combined the DEG and DEL data sets screened from different estrus states and genotypes. The overlap of these two sets was identified to select the mRNAs and lncRNAs that have major effects on ovulation. Among the overlapping molecules, seven DEGs and four DELs were involved in the follicular–luteal transition regulated by FecB mutation. Functional annotation analysis showed that two DEGs (FKBP5 and KITLG) were enriched in melanogenesis, oxytocin and GnRH secretion. LINC-219386 and IGF2-AS were highly expressed in the BB ewes compared with WW ewes, modulating their target genes (DMXL2 and IGF2) to produce more GnRH during follicular development, which explains why mutated ewes produced more mature follicles. These results from expression profiling of the hypothalamus with the FecB mutation at different estrus states provide new insights into how the hypothalamus regulates ovulation under the effect of the FecB mutation.